PELAKSANAAN PERNIKAHAN DI KUA KOTA BENGKULU PASCA PENETAPAN PP No 48 TAHUN 2014 - Yusmita, Yusmita (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: marriage order for the Islamic community every marriage must be recorded, which is carried out by the Marriage Registrar. Every marriage must take place before and under the supervision of a Marriage Registrar, and be proven by a Marriage Certificate. The purpose of this study is to find out how marriage is carried out at KUA in Bengkulu City after the issuance of PP No. 48 of 2014. This research is field research. The type of this research approach is descriptive-qualitative. Data collection techniques with interviews and documentation. The results of this study show that the implementation of marriage at the KUA office after PP No. 48 of 2014 was warmly welcomed, especially by the KUA and in general by the community in Bengkulu City, where before this PP was ratified, the community accused of marriage fees at the KUA, they were worried that there would be graft on these costs, but after the PP was issued, it was clear who had if you want to get married outside the office, you will be charged Rp. 600,000, the payment is through the bank by the married couple themselves, but those who want to get married at their KUA office are not charged at all ( free ), with the clarity of this regulation, the interest of the people in the city of Bengkulu to get married in the office is still lacking, even though there is no fee. there are still many who marry outside the office or at home even though they pay quite a lot of money. Keywords: Marriage Executor, KUA, PP No 48 of 2014 Abstrak: Ketertiban perkawinan bagi masyarakat Islam setiap perkawinan harus dicatat, yang dilakukan oleh Pegawai Pencatat Nikah. Setiapper kawinan harus dilangsungkan di hadapan dan di bawah pengawasan Pegawai Pencatat Nikah, dan dibuktikan dengan Akta Nikah. Tujuan penelitian ini mengetahui bagaimana pelaksanaan nikah pada KUA di Kota Bengkulu pasca keluarnya PP No. 48 Tahun 2014. Penelitian ini merupakan penelitian lapangan (field research). Adapun jenis pendekatanpenelitian ini adalah deskripitif-kualitatif. Teknik pengumpulan data dengan wawancara dan dokumentasi. Hasil penelitian ini menunjukan pelaksanaan nikah di kantor KUA setelah PP No. 48 Tahun 2014 ini keluar disambut baikk hususnya pihak KUA maupun umumnya pihak masyarakat di Kota Bengkulu, dimana sebelum PP ini di sahkan tuduhan masyarakat terhadapbiaya nikah di KUA mahal dan ada kekhawatiran terjadi grafitasi terhadap biaya tersebut, namun setalah PP itu dikeluarkan maka sudah jelas bagi siapa yang mau manikah diluar kantor di kenakan biaya Rp. 600.000 yang pembayaran tersebut melaluai Bank oleh pasangan yang menikah itu sendiri, namun yang mau menikah di kantor KUA mereka tanpa dikenakanbiaya sedikitpun (gratis), dengan kejelasan Peraturan ini minat masyarakat di kota Bengkulu untukmenikah di kantor masih kurang walaupun tanpa biaya, bahkan masih banyak yang menikah di luar kantor atau di rumah meskipun mereka membayar uang yang cukupbesar. Kata kunci: Pelaksana Pernikahan, KUA, PP No 48 Tahun 2014